2016
DOI: 10.1098/rspb.2015.2879
|View full text |Cite
|
Sign up to set email alerts
|

Invader or resident? Ancient-DNA reveals rapid species turnover in New Zealand little penguins

Abstract: The expansion of humans into previously unoccupied parts of the globe is thought to have driven the decline and extinction of numerous vertebrate species. In New Zealand, human settlement in the late thirteenth century AD led to the rapid demise of a distinctive vertebrate fauna, and also a number of 'turnover' events where extinct lineages were subsequently replaced by closely related taxa. The recent genetic detection of an Australian little penguin (Eudyptula novaehollandiae) in southeastern New Zealand may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Ancient DNA data are rapidly expanding this appreciation of extinction‐recolonization dynamics. For instance, a number of recent aDNA studies have revealed abrupt biological “turnover” events, with extinct lineages apparently being rapidly replaced by exotic lineages via trans‐oceanic dispersal . In some cases, the colonization events appear to have masked the decline of endemic lineages (Fig.…”
Section: Ancient Dna Reveals Cryptic Invasions and Rapid Range‐shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancient DNA data are rapidly expanding this appreciation of extinction‐recolonization dynamics. For instance, a number of recent aDNA studies have revealed abrupt biological “turnover” events, with extinct lineages apparently being rapidly replaced by exotic lineages via trans‐oceanic dispersal . In some cases, the colonization events appear to have masked the decline of endemic lineages (Fig.…”
Section: Ancient Dna Reveals Cryptic Invasions and Rapid Range‐shiftsmentioning
confidence: 99%
“…Diagram depicting the recent (ca. 400 ya) establishment of Eudyptula novaehollandiae in southern New Zealand following human‐mediated extirpation of southern populations of the endemic Eudyptula minor , as inferred from ancient‐DNA analysis . Blue and red borders interpolate distributions of E. minor and E. novaehollandiae , respectively.…”
Section: Ancient Dna Reveals Cryptic Invasions and Rapid Range‐shiftsmentioning
confidence: 99%
“…New Zealand's rich archaeological record [24] presents intriguing opportunities to unravel the often complex dynamics between human populations and indigenous wildlife [25][26][27][28][29][30][31]. Recent analyses of ancient DNA (aDNA) have led to paradigmatic shifts in our understanding of the evolution of NZ's biota [32].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent failure of coalescent analyses (based on small numbers of loci) to accurately recover recent founder events has previously been noted for another newly arrived New Zealand bird ( Eudyptula novaehollandiae ) where initial modelling (Peucker, Dann, & Burridge, ) yielded founding timeframe estimates substantially older than the anthropogenic event directly detected by ancient DNA (Grosser et al., ) and also recovered by multilocus modelling using time‐dependent rates (Grosser, Burridge, Peucker, & Waters, ). Broadly, we suggest that the outputs of such analyses should be interpreted with caution, particularly when assessing recent demographic and range shifts.…”
mentioning
confidence: 96%